Particulate Air Pollution in Central Serbia and some Proposed Measures for the Restoration of Degraded and Disturbed Mining Areas - Mihalj, Ivana; Šušak, Stamenko; Palanački Malešević, Tamara; Važić, Tamara; Jurca, Tamara; Pavić, Dragoslav; Simeunović, Jelica; Vulin, Aleksandra; Meriluoto, Jussi; Svirčev, Zorica (Geographica Pannonica, 2024)
Mining causes soil degradation, particle emission, and air and water quality deterioration. This study estimates some health risks in districts of Central Serbia af fected by surface mining activities, and proposes measures for land restoration. The epidemiological risk assessment was based on data for seven cancers and three cardiovascular diseases during 2010 - 2020. Results showed a statistically significant increase in the incidence of lung and bronchial cancer in critical districts. Borski district stood out with the highest incidence rates for cardiovascular diseases. The suspected role of particulate air pollution from the mining industry in health deterioration calls for intensified air quality monitoring and development of mitigation technologies. A restoration strategy called the Pan-Life-Carpet technology is proposed for the restoration of mining areas and for air and water pollution control.
Keywords: mining areas, land restoration, air pollution, particulate matter, biocrusts, cyanobacteria